The prrF -Encoded Small Regulatory RNAs Are Required for Iron Homeostasis and Virulence of Pseudomonas aeruginosa - Alexandria A. Reinhart; Daniel A. Powell; Angela T. Nguyen; Maura O’Neill; Louise Djapgne; Angela Wilks; Robert K. Ernst; Amanda G. Oglesby‐Sherrouse (2014)
Pseudomonas aeruginosa is an opportunistic pathogen that requires iron to cause infection, but it also must regulate the uptake of iron to avoid iron toxicity. The iron-responsive PrrF1 and PrrF2 small regulatory RNAs (sRNAs) are part of P. aeruginosa's iron regulatory network and affect the expression of at least 50 genes encoding iron-containing proteins. The genes encoding the PrrF1 and PrrF2 sRNAs are encoded in tandem in P. aeruginosa, allowing for the expression of a distinct, heme-responsive sRNA named PrrH that appears to regulate genes involved in heme metabolism. Using a combination of growth, mass spectrometry, and gene expression analysis, we showed that the ΔprrF1,2 mutant, which lacks expression of the PrrF and PrrH sRNAs, is defective for both iron and heme homeostasis. We also identified phuS, encoding a heme binding protein involved in heme acquisition, and vreR, encoding a previously identified regulator of P. aeruginosa virulence genes, as novel targets of prrF-mediated heme regulation. Finally, we showed that the prrF locus encoding the PrrF and PrrH sRNAs is required for P. aeruginosa virulence in a murine model of acute lung infection. Moreover, we showed that inoculation with a ΔprrF1,2 deletion mutant protects against future challenge with wild-type P. aeruginosa. Combined, these data demonstrate that the prrF-encoded sRNAs are critical regulators of P. aeruginosa virulence.